Ocena dostawców jako element controllingu zaopatrzenia w małych i średnich przedsiębiorstwach - Dyczkowska, Joanna (Evaluation as an Element of Suppliers Controlling in Small and Medium Enterprises., 2006)
The paper focuses on pointing out and characterizing various methods of evaluation of existing and potential suppliers by small and medium enterprises. The author indicates not only possibilities of the application of particular methods but also constraints related to the shortage of information. The article intends eventually to stimulate discussion among business professionals in charge of supplying policy on other applicable solutions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 15-22